Procesul de producție al produselor farmaceutice veterinare - Crida Pharm - Gabriel Badic (Medicamentul Veterinar)
The presentation is a description of CridaPharm, a leading Romanian company where the latest achievements in compliance with European regulations, GMP, and ISO 9001-015 are presented. The stages of the manufacturing process in the six production sections are presented. Medicines production section in the form of injectable solutions packaged in sterile polypropylene and glass vials, oral solutions, intramammary syringes, powder medications production department, granular premix and powder micronization, and tablets section.